2013
DOI: 10.1097/sla.0b013e31829654f3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury, Renal Function, and the Elderly Obese Surgical Patient

Abstract: Objective To investigate the association between obesity and perioperative acute kidney injury (AKI), controlling for preoperative kidney dysfunction. Summary Background Data More than 30% of patients over the age of 60 are obese, and therefore at risk for kidney disease. Post-operative AKI is a significant problem. Methods We performed a matched case control study of patients enrolled in the Obesity and Surgical Outcomes Study (OBSOS), using Medicare claims data enriched with detailed chart review. Each A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
6
34
1
Order By: Relevance
“…These subjective conclusions were offered despite the documented 4.42 times greater dislocation rate in the group with a BMI of 35 kg/m 2 or greater. Our data do not support a continuous increase in renal failure as previously reported [11][12][13]. Our data do correspond to that of Hanly et al [10] who reported a 12.8%, 30-day readmission rate.…”
Section: Discussioncontrasting
confidence: 88%
“…These subjective conclusions were offered despite the documented 4.42 times greater dislocation rate in the group with a BMI of 35 kg/m 2 or greater. Our data do not support a continuous increase in renal failure as previously reported [11][12][13]. Our data do correspond to that of Hanly et al [10] who reported a 12.8%, 30-day readmission rate.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding corroborates those of several other studies showing that higher BMI is associated with increased risk for AKI in the postoperative setting (Kelz et al, 2013;Schmid et al, 2014). A possible explanation may be that obesity may predispose patients to AKI postoperatively because volume assessment and resuscitation is more difficult in the obese patient, which places patients at risk for pre-renal AKI (Kelz et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Several pre-and perioperative risk factors for developing AKI after abdominal surgery have been reported, including age, obesity, hypertension, COPD, elevated preoperative SCr level, and more Revised Cardiac Risk Index risk factors, although studies have yielded somewhat discordant results. 13,15,16,30 After multivariate adjustment, female sex, hypertension, preoperative CKD, ASA physical status classification of IV or V, and reoperation were identified as independent risk factors for AKI. The strong association of the commonly used perioperative mortality and cardiac morbidity risk indices with AKI is of special interest and further demonstrates their usefulness in the overall perioperative risk assessment.…”
Section: Discussionmentioning
confidence: 99%